ANALISIS BEBAN KERJA DAN KEBUTUHAN TENAGA PRAMUBAKTI DENGAN METODE WORK SAMPLING DAN METODE WORKLOAD INDICATOR STAFF NEEDES - Dhiana Ekowati; Isro Subekti (Kajian Ekonomi dan Bisnis, 2022)
One of the important components for calculating power requirements is the workload. This means that the determination of power requirements is adjusted to the existing workload. The Workload Indicator Staff Needs (WISN) method is a method for calculating the workforce needs based on the actual workload carried out by the workforce. This study aims to analyze the workload of services using the Work Sampling technique and analyze the needs of service workers using the WISN method. This research was carried out in the Surgery and Anesthesia Room Installation, Dr. Sardjito. This type of research is descriptive qualitative by conducting observations, in-depth interviews and document review. The results showed that the use of time for productive activities was 71.11%, the use of time for non-productive activities was 9.36% and the use of time for personal activities was 19.53%. The results of the calculation of the need for energy using the WISN method show the number of service staff as many as 20 people with a WISN ratio of 0.75. From the results of this study, it is suggested to the management of Dr. Sardjito to consider adding a staff of 5 people according to the existing workload